GOLD IN ORE ASSOCIATIONS IN AREAS OF MARGINAL ANDESITE BELTS (AS ILLUSTRATED BY THE URALS) - Sazonov V.N.; Murzin V.V.; Grigoryev N.A. (My University, 1990)
The area of andesite belts in the Urals is east of the Ural paleo-oceanic region. It has already been established that complexes of different age in this area coincide in space, and that each of them includes specific ore associations with different levels of gold concentration. The latter trend was briefly analyzed earlier. Here we shall discuss it in greater detail on the basis of new data obtained recently. The distribution pattern of ore mineralization around intrusions (Fig. 2), as well as the radiometric age of metasomatites around ore bodies (skarn 340, beresite and listvenite 345 to 335, and quartz-sericite metasomatite 300 m.y.), indicate that such mineralization was deposited in the regressive stage of TMR as a result of repeated reactivation of the faults controlling that process.